TARABA SERVICIILOR DE BIBLIOTECĂ - HARJEVSCHI, director general, Biblioteca Municipală „B.P. Hasdeu”, Mariana (BIBLIOPOLIS, 2020)
On October 19, 2016, the Municipal Library “B.P. Hasdeu” celebrated 139 years. This anniversary was organized in a creative way for the library community and to the library users. It went hand in hand with the aspirations and needs of the Chisinau community by following informal settings. Thus, a special event was entitled the Library Service Booth. It’s a call that has shown what can be done in a modern library. The event took place within the framework of the national campaign See you at the library!, supported by the Novateca program and the Ministry of Culture, which aimed to inform the public about the fact that the libraries in the Republic of Moldova to become vibrant community centers where every citizen, regardless of age and occupation, can benefit from modern services and interactive activities.